2023
DOI: 10.3389/fmmed.2022.1035290
|View full text |Cite
|
Sign up to set email alerts
|

Whole patient knowledge modeling of COVID-19 symptomatology reveals common molecular mechanisms

Abstract: Infection with SARS-CoV-2 coronavirus causes systemic, multi-faceted COVID-19 disease. However, knowledge connecting its intricate clinical manifestations with molecular mechanisms remains fragmented. Deciphering the molecular basis of COVID-19 at the whole-patient level is paramount to the development of effective therapeutic approaches. With this goal in mind, we followed an iterative, expert-driven process to compile data published prior to and during the early stages of the pandemic into a comprehensive CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 312 publications
0
10
0
Order By: Relevance
“…A full analytical overview of the generated model is summarized in Supplementary Table S1 and made available via our COVID-19 Explorer. In addition, extended information about specific mechanisms, pathways, clinical phenotypes and insights into the clinico-molecular hypotheses derived from our model are reported in the associated back-to-back publication ( Brock et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…A full analytical overview of the generated model is summarized in Supplementary Table S1 and made available via our COVID-19 Explorer. In addition, extended information about specific mechanisms, pathways, clinical phenotypes and insights into the clinico-molecular hypotheses derived from our model are reported in the associated back-to-back publication ( Brock et al, 2022 ).…”
Section: Introductionmentioning
confidence: 91%
“…Here, we report on our findings and the functionality of the COVID-19 Explorer web resource. Our results are provided at the level of a whole-patient knowledge model, including the possible causative pathogenic mechanisms underlying COVID-19 phenotypes ( Brock et al, 2022 ). To accommodate usability for a variety of use-case scenarios, results are summarized in different formats: the ‘COVID-19 Explorer’ provides a detailed, comprehensive and fully interactive view of the relationships and accompanying evidence, while ‘The COVID-19 Cockpit’ (see Supplementary Table S1 ) is intended to support clinical researchers in diagnostic and hypothesis generation for new therapeutic strategies (see Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The resultant whole-patient model (available at http://covid19.molecularhealth.com, accessed on 8 January 2023) revealed that SARS-CoV-2 perturbs eight core pathogenic processes: inflammatory signaling, coagulation, barrier permeability, senescence, autoimmunity, fibrogenic signaling, nociception and exocytosis [95]. Together, these mechanisms were proposed to be responsible for unleashing a pathogenesis spectrum, ranging from 'a perfect storm' triggered by acute hyper-inflammation to chronic fatigue in protracted COVID-19 syndromes.…”
Section: Application Of Hd 3 To Drug Repositioning and Combinatorial ...mentioning
confidence: 99%